Theological Legacy of a Church Historian: Prof. Hristo Stoyanov - Pavlov, Pavel (Forum Theologicum Sardicense, 2025)
This article is dedicated to the life and legacy of Professor Hristo Stoyanov as a church theologian, teacher, and researcher of Church history. It addresses the significance of continuity between generations within church-theological circles and the challenges of maintaining this continuity under Bulgarian political conditions. The article highlights the individual’s commitment to upholding the Truth and the Christian faith during the totalitarian communist regime, emphasizing the crucial role of history and faith in shaping both human and Christian identity.